Physics of the stoics - Sambursky, Samuel, 1900- (Princeton legacy library., 1959)
Stoic physics, based entirely on the continuum concept, is one of the great original contributions in the history of physical systems. Building on The Physical World of the Greeks, the author describes the main aspects of the Stoic continuum theory, traces its origins back to pre-Stoic science and philosophy, and shows the attempts of the Stoics to work out a coherent system of thought that would explain the essential phenomena of the physical world by a few basic assumptions. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand techn.